Influence of Divalent Cation Doping on the Structural, Subsolidus Solubility and Electrical Properties of Bismuth Copper Niobate Pyrochlores - Chon, M. P.; Feng, Y.; Raman, V.; Lim, T. Z.Alvin; Kechik, M. M.A.; Khaw, C. C.; Ghotekar, S.; Chan, K. Y.; Murthy, H. C.Ananda; Lu, M.; Zhou, D.; Tan, K. B. (Springer, 2025)
This study presents a comprehensive analysis of the subsolidus solubility, structural and electrical properties of divalent cation-doped bismuth copper niobate (BCN) pyrochlores, achieved through selective A- or B-site substitution. BCN pyrochlores, recognised for their low sintering temperatures and superior dielectric properties, were doped with Ni2+, Zn2+, Ca2+ and Pb2+ to improve their electrical performance. These pyrochlores were synthesised via meticulous solid-state reaction and extensively characterised using X-ray diffraction (XRD), scanning electron microscopy (SEM), inductively coupled plasma-optical emission spectroscopy (ICP-OES), impedance spectroscopy and thermal analysis. Our findings indicate limited solid solution formation, with solubility limits varying depending on the dopant. The electrical conductivity increased with doping, attributed to oxygen vacancies and varying copper oxidation states; the Ca-doped BCN pyrochlores exhibited the highest conductivity. These thermally stable BCN pyrochlores exhibited dielectric constants ranged from approximately 40 to 110, varying with dopant concentration, while their dielectric losses remained relatively high. This research also demonstrates the potential of divalent cation doping to optimise BCN pyrochlores for advanced dielectric applications, while emphasising the critical need for precise compositional control to maintain a balance between electrical performance and structural stability.